Contextual Conditions of Public Health Implementation: Exploring the Tensions of Strategic and Operative Work - Albin Algotson; David Ekholm; Ulrika Müssener (Nordisk Välfärdsforskning)
This article addresses the contextual conditions for the implementation and development of public health work in local government administration. Given the crucial role of local governments in fostering holistic, community-based health strategies, the integration of public health initiatives into local political and administrative structures remains under-emphasized in both practice and research. Through focus group interviews in six municipalities, the study explores the institutional and organizational boundaries that shape the political and administrative context of local public health work. The findings reveal a gap between the strategic, municipality-wide work and the operational work focused on children and youth within welfare services, such as schools and social services. The challenges in implementing and developing local working methods for public health work in relation to the sectorized administration are particularly identified. This challenge is understood as a tension between traditional, sectorized welfare policies and cross-sectoral public health policies. The analysis underscores that a thorough understanding of the political and administrative context is essential for building effective public health strategies. The article advocates viewing local public health work as a dynamic process, emphasizing the importance of managing change rather than establishing a fixed order. Furthermore, we emphasize the significant need for continued practice-oriented research to develop an understanding of local public health work by integrating knowledge of interventions and medical aspects of health with contextual and implementation-oriented knowledge of the institutional and organizational conditions within local government organizations.